ANALISIS MEDIA RELATIONS KOMISI PEMILIHAN UMUM (KPU) SULAWESI TENGAH - Israwaty Suriady; Fitriani Puspa Ningsih; Giska Mala Rahma Rini; Farin Firda Savhira (Kinesik, 2023)
This study describe Media Relations activities and strategies of Central Sulawesi's Komisi Pemilihan Umun (KPU). This study is qualitative based on descriptive research. Data collection techniques used in this study are observation, documentation, and interviews with four (4) selected informants through purposive sampling technique. The data analysis technique used is an interactive analysis model consisting of data reduction, data display and drawing conclusions. The results indicate that Media Relations activities of Central Sulawesi KPU consists of Press Release and Press Events. Media Relations Strategies implemented namely: customer service and provision of services information through the PPID facility, website, or personal contact; maintenance the good reputation and trust of journalists through the presentation of complete information, accurate and impartial; sending manuscript copy and attempt to meet the criteria of good news and press release through journalism training; cooperate in the implementation of press events in the form of coordination and provision of pre- activity materials; provide verification facility through Media Center, website and PPID, as well as material facilities such as accommodation, rooms and wi-fi; and building personal relationships with journalists through interaction and communication outside working hours.